Risk Factors Related to Acute Radiation Dermatitis in Breast Cancer Patients After Radiotherapy: A Systematic Review and Meta-Analysis - Xie, Yuxiu; Wang, Qiong; Hu, Ting; Chen, Renwang; Wang, Jue; Chang, Haiyan; Cheng, Jing (Frontiers in Oncology, 2021)
Background: Acute radiation dermatitis (ARD) negatively affects patients’ quality of life. Some studies have reported several risk factors that can predict breast cancer patients at a high risk of ARD. This study aimed to identify risk factors associated with ARD. Methods: PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, and Wanfang literature databases were searched. The pooled effect sizes, relative risks (RRs) and 95% confidence intervals (CIs), were calculated using the random-effects model. Potential heterogeneity and sensitivity analyses were also performed. Results: A total of 38 studies comprised of 15,623 breast cancer patients were included in the analysis. Of the seven available patient-related risk factors, four factors were significantly associated with ARD: body mass index (BMI) ≥25 kg/m² (RR = 1.11, 95% CI = 1.06–1.16), large breast volume (RR = 1.02, 95% CI = 1.01–1.03), smoking habits (RR = 1.70, 95% CI = 1.24–2.34), and diabetes (RR = 2.24, 95% CI = 1.53–3.27). We found that hypofractionation reduced the risk of ARD in patients with breast cancer compared with that in conventional fractionated radiotherapy (RR = 0.28, 95% CI = 0.19–0.43). Sequential boost and bolus use was significantly associated with ARD (boost, RR = 1.91, 95% CI = 1.34–2.72; bolus, RR = 1.94, 95% CI = 1.82–4.76). However, chemotherapy (RR = 1.17, 95% CI = 0.95–1.45), hormone therapy (RR = 1.35, 95% CI = 0.94–1.93), trastuzumab therapy (RR = 1.56, 95% CI = 0.18–1.76), and nodal irradiation (RR = 1.57, 95% CI = 0.98–2.53) were not correlated with ARD. Sensitivity analysis results showed that BMI was consistenly associated with ARD, while smoking, breast volume, and boost administration were associated with ARD depending on study design, regions and toxicity scale used. Hypofractionation is consistently shown as protective. The differences between study design, toxicity scale, and regions may explain little of the sources of heterogeneity. Conclusion: The results indicated that BMI was a significant predictor of ARD and that hypofractionation was consistently protective. Depending on country of study, study design, and toxicity scale used, breast volume, smoking habit, diabetes, as well as sequential boost and bolus use were also predictive of ARD.